Artificial Intelligence Ethics within Christian Pedagogy: Reconstructing Faith Based Educational Discourses in the Era of Algorithmic Culture - Marthen Mau; Warlina Hulu; Syarah Yakoba Idamaris Faot (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The rapid integration of Artificial Intelligence (AI) in education presents both opportunities and ethical challenges, especially for faith based institutions such as Christian schools. These institutions must balance technological innovation with their theological commitments. As AI becomes more embedded in educational environments, Christian educators face the challenge of integrating AI in a way that aligns with Christian values, human dignity, and relational teaching roles. This study explores how Christian moral teachings can guide the integration of AI into education, providing a framework for ethical AI use in Christian schools. Previous studies have highlighted the ethical concerns associated with AI, including algorithmic bias, data privacy, and the potential for AI to undermine relational teaching roles. Christian educational theology, which emphasizes values such as human dignity, justice, and fairness, offers a robust framework for addressing these concerns. A biblical worldview and the concept of Imago Dei (the image of God) provide theological foundations for integrating AI ethically in education, ensuring that AI tools enhance human centered learning rather than replace human educators. Additionally, literature suggests that ethical guidelines informed by Christian teachings can mitigate AI's ethical risks and promote a more inclusive and equitable educational environment. This study employs a mixed methods approach, combining qualitative and quantitative research methods. The qualitative phase involves document analysis and interviews with Christian educators and theologians to explore theological reflections on AI and its ethical implications.